Home and Neighborhood Context and Fall Risk Among Older Americans. (16th December 2020) - Okoye, Safiyyah; Mulcahy, John; Fabius, Chanee; Wolff, Jennifer
Abstract: Falls result from complex interactions between individuals and their environment and are the leading cause of injuries among older adults. A nascent literature demonstrates an association between neighborhood characteristics and falls. However, available evidence is from small, nonrepresentative samples and generally focuses on individual, home, or neighborhood risk-factors rather than the contribution of all three. We link information from N=6, 489 community-dwelling participants in the 2015 National Health and Aging Trends Study with the Social Deprivation Index (SDI), which yields a census-tract-level score of socioeconomic disadvantage, to assess associations between home and neighborhood context and falls in the previous year. Household financial strain was associated with a 31% increased risk of falling, and indoor trip hazards with a 14% increased risk, after adjusting for individual factors and neighborhood SDI (all p <0.05). Findings reflect the interplay between home and neighborhood context and fall-risk, and can inform community-based fall-prevention interventions.